N4‐Acetylcytidine‐Mediated CD2BP2‐DT Drives YBX1 Phase Separation to Stabilize CDK1 and Promote Breast Cancer Progression - Hongyu Wang; Bozhi Zhao; Jiayu Zhang; Qunyu Hu; Linlin Zhou; Yinghui Zhang; Yixin Cai; Yuansong Qu; Tao Jiang; Dongwei Zhang (Advanced Science)
Abstract Long noncoding RNAs (lncRNAs) play critical roles in the initiation and progression of breast cancer. However, the specific mechanisms and biological functions of lncRNAs in breast cancer remain incompletely understood. Bioinformatics analysis identifies a novel lncRNA, CD2BP2‐DT, that is overexpressed in breast cancer and correlates with adverse clinicopathological features and poor overall survival. Both in vivo and in vitro experiments demonstrate that CD2BP2‐DT promotes proliferation of breast cancer cells. Mechanistically, NAT10 mediates the N4‐acetylcytidine (ac4C) modification of CD2BP2‐DT, enhancing its RNA stability and expression. More importantly, CD2BP2‐DT enhances the stability of CDK1 mRNA by mediating YBX1 phase separation, thereby promoting the proliferation of breast cancer cells. In conclusion, the lncRNA CD2BP2‐DT is identified as a crucial driver of breast cancer cell proliferation through the YBX1/CDK1 axis, highlighting its potential as a promising biomarker and therapeutic target for breast cancer.